Health education provided by the nurse to the career in the light of ecosystem thinking (Research, Society and Development, 2020)
To analyze, in the view of the caregiver, the health education provided by nurses during the hospitalization period of the user with non-communicable chronic disease for the continuity of care at home, in the light of Ecosystem Thinking. Descriptive, exploratory and qualitative research. Data collection by semi-structured interview. The analysis followed the thematic analysis method steps. Educational actions are not seen as inherent attributes of nurses' work practice and, when performed by nurses, are piecemeal and anchored in the biomedical health model. Health education, provided by nurses, needs to transcend the limitations of the Cartesian, prescriptive and deterministic model. It is recommended to anchor health actions in the principles of Ecosystem Thinking, based on their systemic and contextualized understanding, enabling the gaps pointed out by the caregivers of this research to be overcome.